ACCORDANCE SYSTEM OF DISTANCE LEARNING “FOUNDATIONS OF ALGORITHMIZATION AND PROGRAMMING” TO INTERNATIONAL STANDARDS OF QUALITY - Bakumenko, E. (Journal of Information Technologies in Education (ITE), 2009)
In the article is examined accordance of the integrated environment of study course «Foundations of algoritmization and programming» with the requirements of international standards of quality IMS and SCORM for distance learning systems.